Re-Clustering and Profiling of Digestive System Tumors According to Microenvironment Components - Wang, Yongwei; Guo, Sen; Chen, Zhihong; Bai, Bing; Wang, Shuo; Gao, Yaxian (Frontiers in Oncology, 2021)
Background: Immunotherapy has become the most promising therapy in digestive system tumors besides conventional chemotherapy and radiotherapy. But only a few patients can benefit from different types of immunotherapies, such as immune checkpoint blockade (ICB). To identify these ICB-susceptible patients, methods are urgently needed to screen and profile subgroups of patients with different responsiveness to ICB. Methods: This study carried out analysis on patients with digestive system tumors that were obtained from Cancer Genome Atlas (TCGA) cohorts. The analyses were mainly performed using GraphPad Prism 7 and R language. Results: We have quantified the microenvironmental components of eight digestive system tumor patients in TCGA cohorts and evaluated their clinical value. We re-clustered patients based on their microenvironment composition and divided these patients into 6 clusters. The difference between these 6 clusters were profiled, including survival conditions, enriched biological processes, genomic mutations and microenvironment traits. Cluster 3 was the most immune-related cluster, exhibiting a high infiltration of non-tumor components and poor survival status, along with an inhibitory immune status. And we found that patients with high stromal score indicated a poor response in ICB cohort. Conclusions: Our research provides a new strategy based on the microenvironment components for the reclassification of digestive system tumors, which could provide guidance for prognosis judgment and treatment response prediction like ICB.